Effects of nandrolone decanoate and resistance exercise on skeletal muscle in adult male rats - Cruz, Cynthia Dela; Agati, Leandro B. [UNESP]; Pereira, Oduvaldo C.M. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
The aim of this study was to compare the effects of resistance exercise associated or not with nandrolone decanoate (ND) on skeletal muscles and body mass of adult male rats. Training protocol consisted of 15 jump sessions, for 6 weeks. ND (5mg/kg) was administered twice a week. The exercise was effective in inducing respective enlargements in fiber areas of extensor digitorum longus and soleus muscles. ND associate with exercise was also able to induce increases in fiber areas these muscles. In untrained group that received nandrolone decanoate an improved in muscular parameters could be observed. In conclusion, the resistance exercise was able to promote an enlargement in fiber areas of both muscles studied without ND treatment, indicating that after a period of time of adaptation to exercise, the muscular effects caused by ND could be achieved in the same way by exercise, without ND and without risks for health.
Efectos del decanoato de nandrolona y el ejercicio de resistencia en el músculo esquelético de ratas machos adultos
Keywords: Anabolic Androgenic Steroids; Extensor Digitorum Longus; Nandrolone Decanoate; Resistance Training; Skeletal Muscles; Soleus